FRAGILITY PROFILE OF ELDERLY CARE IN PRIMARY HEALTH CARE. - Luciano da Silva, Josefa Raquel; da Silva Júnior, José Antonio; de Sales Melo, Mayse Cristelle; Pereira Chaves, Ana Elisa; de Araújo Leite Medeiros, Fabíola; Torres de Medeiros, Ana Claudia (Revista de Pesquisa: Cuidado é Fundamental)
Objective: to evaluate the prevalence and degrees of frailty in the elderly cared for in Primary Health Care, through the Edmonton Frail Scale. Method: The data were obtained through a previously prepared questionnaire. Except for sample losses and refusals, 118 elderly people participated in the study. Data collection was performed at the Basic Health Unit or at the elderly's home. Results: Among the 118 elderly people interviewed, there was a predominance of females (72%), the average age was approximately 71.55, corroborating also with other studies. Over these, the low level of education stood out. Regarding frailty in general, 28% (n = 3) of the interviewees obtained scores common to frailty, 32.2% (n = 38) were considered apparently vulnerable and 39.8% (n = 47) were not fragile. Conclusion: In view of the changes that the frail elderly can undergo with the progress of this problem, early interventions are needed that Primary Health Care is able to prioritize, however further studies are needed to assess variables related to frailty in different types of people.